PENGARUH KUALITAS BIJI KOPI ROBUSTA TERHADAP HARGA PASAR DI MEKAKAU ILIR OKU SELATAN - Saiful Bahrie (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research were to : (1) To determine farm income of coffee beans in the village of New Water District of Mekakau Ilir Kabupaten South OKU, (2) To determine the effect of the quality of the coffee beans to the market price in the village of New Water District of Mekakau Ilir Kabupaten South OKU. This research was conducted in the village of New Water District of Southern OKU Mekakau Ilir Kabupaten. The choice of location is done deliberately because it is the central area of coffee production in the district of South OKU. Course of a study conducted in April to June 2015, with the survey and observation. This study found that There are differences in income between coffee farming with treatment and farming of red fruit picking coffee with yellow fruit picking treatment. Coffee farming income with red fruit bigger than a coffee farm income with yellow fruit and coffee farming with more menguntungkan.dibandingkan red fruit with yellow fruit coffee farming.